Navigating the Road to Reintegration Status and Continuing Support of the U.S. Air Force's Wounded Warriors - Sims, Carra S. (RAND Corporation, 2015)
To help the U.S. Air Force gain greater insight into the well-being of its members who have sustained mental or physical injuries in combat or combat-related situations, this report gauges the current status of the Air Force's wounded warriors, including their use of and satisfaction with Air Force programs designed to serve them. It presents the baseline findings from a longitudinal analysis of enrollees in the Air Force Wounded Warrior program who were receiving benefits or undergoing evaluation to receive benefits.